1997
DOI: 10.1111/j.1524-4725.1997.tb00014.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycolic Acid Peels for Postinflammatory Hyperpigmentation in Black Patients

Abstract: This pilot study demonstrates that serial glycolic acid peels provide an additional benefit, with minimal adverse effects, for the treatment of postinflammatory hyperpigmentation in dark-complexioned individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 11 publications
3
73
0
2
Order By: Relevance
“…Burns et al 22 assessed 19 patients (SPT IV-VI) with PIH who were randomized to either of two groups. The control group was managed with 2% hydroquinone/10% glycolic acid gel twice daily, with 0Á05% tretinoin at night.…”
Section: Glycolic Acid and Postinflammatory Hyperpigmentationmentioning
confidence: 99%
“…Burns et al 22 assessed 19 patients (SPT IV-VI) with PIH who were randomized to either of two groups. The control group was managed with 2% hydroquinone/10% glycolic acid gel twice daily, with 0Á05% tretinoin at night.…”
Section: Glycolic Acid and Postinflammatory Hyperpigmentationmentioning
confidence: 99%
“…Since Kligman et al [10] reported that the combined use of topical atRA, dexamethasone, and hydroquinone was more effective as a depigmenting formulation than a single use of each reagent, hydroquinone has been widely used in combination with atRA and corticosteroid [4,18]. Furthermore, in recent years, hydroquinone has been used in combination with laser therapies [1,2,8], dermabrasion [20], and chemical peelings such as Jessner's solution and glycolic acid [3,5,13,14]. Although Kligman's mixture is well-known and widely used, the bleaching ability is weak and a prolonged period of treatment is required, with variable clinical results.…”
mentioning
confidence: 99%
“…In a number of previous studies [2,3,5,6,8], the L* value has been utilized as an index of skin pigmentation. However, there was only a weak correlation between the L* value and the melanin index detected in normal skin [7].…”
Section: Discussionmentioning
confidence: 99%